ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
The development of organic photocatalysts holds considerable promise for the oxidation of NADH, thereby disrupting the NADH/NAD+ equilibrium, modulating redox homeostasis, and enhancing treatment of hypoxic tumors. However, there is still a lack of organic photocatalyst which could respond to near-infrared light. Herein, we develop an NIR-triggered organic photocatalyst (TTH) that produces hydroxyl radical and photooxidates NADH. Upon 808 nm light irradiation, TTH not only could generate hydroxyl radical in an optimized pathway of O 2 →O 2 • - →H 2 O 2 →•OH and achieve effective oxidation of NADH and the reduction of cytochrome c, but also produces hyperthermia, facilitating NIR-II fluorescence-guided phototherapy of tumors. Moreover, TTH preferentially degrades glutathione, increases lipid peroxide levels, and downregulates glutathione peroxidase 4, culminating in mitochondrial dysfunction and the initiation of ferroptosis‑like cell death. Subsequently, the in vivo experiments proved that the photocatalytic TTH achieved antitumor efficacy in 4T1-bearing mouse models. Collectively, our research highlights the potential of employing an NIR-activated organic photocatalyst to integrate phototherapy with hydroxyl radical generation, representing a promising therapeutic strategy to disrupt intracellular redox homeostasis for the treatment of tumors.